EXPERIENCE OF USE OF DTAP HEXAVACCINE AT THE VACCINAL PREVENTION UNIT FOR CHILDREN WITH HEALTH DEVIATIONS OF THE SCIENTIFIC CENTER OF CHILDREN’S HEALTH (FEDERAL STATE BUDGETARY SCIENTIFIC INSTITUTION) - T. A. Grechukha; N. E. Tkachenko; D. A. Novikova; G. A. Gaivoronskaya; L. S. Namazova-Baranova (Педиатрическая фармакология)
Nowadays, parents are anxious about vaccination, as they fear both side effects of vaccines and large numbers of injections. The need in simultaneous administration of 4–5 injections became irrelevant due to development of combined vaccines; it resulted in improved vaccination coverage of children and higher trust of patients in vaccination in whole. The article presents experience of using a hexavaccine at the vaccinal prevention unit for children with health deviations of the Scientific Center of Children’s Health, as well as experience of concurrent immunization of children with a hexavaccine and a 10-valent vaccine against pneumococcal infection. The authors demonstrate that immunization with combined vaccines is safe for children, including premature infants, and reasonable when vaccination schedule has been broken. Moreover, it helps to reduce governmental expenses on immunization. Parents become more loyal vaccination due to the smaller number of injections and absence of adverse reactions.